Navigation of Robotics Platform Using Advanced Image Processing Navigation Methods - Beran Ladislav; Chmelař Pavel; Rejfek Luboš (Taylor & Francis Inc, 2015)
This paper deals with methods suitable for movable robotics platform navigation. We can divide these methods into suitability for indoor navigation, outdoor navigation or its combination. At present, the navigation methods of robotics platforms, suitable for outdoor spaces, are based on GNSS (Global Navigation Satellite System). Accurate position estimation is a big advantage for this type of navigation. Unfortunately this type of navigation is not suitable for indoor spaces and industrial areas, mainly because of the weak signal and low position accuracy. An alternative navigation system is necessary for these solutions – system independent on satellite navigation. Our research is focused on movable robotics platform navigation using advanced image processing methods. Descriptions of these sophisticated methods are presented in this paper.
Navigace robotické platformy za využití pokročilých metod zpracování obrazu
Keywords: Monocular camera vision; image processing; visual odometry; robot navigation; Surface detection; Monokulární kamerové vidění; Zpracování obrazu; Visuální odometrie; Robotická navigace; Deketce objektů